2004
DOI: 10.1111/j.1600-0897.2004.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Antichlamydial and Antisperm Antibodies in Patients with Chlamydial Infections

Abstract: The genital Chlamydia infection may play a role in the induction of ASA. This is probably a result of the inflammatory process, but not of cross-reactivity between sperm and Chlamydia trachomatis antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Opinions about the relevance of ASA in semen, as measured by the mixed antiglobulin reaction (MAR) and immunobead tests in urogenital tract infections are divided. There are reports demonstrating a significantly higher ASA incidence in seminal plasma from patients with prostatitis and epididymitis, as compared with noninflammatory group [130,131]. In contrast to these studies, others suggested the lack of correlation between the presence of ASA and inflammation/infection in semen [132].…”
Section: Role Of the Immune/autoimmune Reactionsmentioning
confidence: 60%
“…Opinions about the relevance of ASA in semen, as measured by the mixed antiglobulin reaction (MAR) and immunobead tests in urogenital tract infections are divided. There are reports demonstrating a significantly higher ASA incidence in seminal plasma from patients with prostatitis and epididymitis, as compared with noninflammatory group [130,131]. In contrast to these studies, others suggested the lack of correlation between the presence of ASA and inflammation/infection in semen [132].…”
Section: Role Of the Immune/autoimmune Reactionsmentioning
confidence: 60%
“…Among the risk factors for ASA production, the chronic inflammatory diseases with different localization are believed to play an important role [5][6][7][8]. The inflammatory response is associated with production of antibodies to spermatozoal and microbial antigens.…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports suggesting that human sperm have antigens that cross‐react immunologically with certain microbial antigens, such as those of C. trachomatis 9–12 . However, this is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first demonstration that Ct infection could play a role in the production of sperm‐immobilizing antibodies in infertile women. Dimitrova et al 12 . previously described that the genital C. trachomatis infection might play a role in the induction of antisperm antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation